2008
DOI: 10.4067/s0718-58392008000100009
|View full text |Cite
|
Sign up to set email alerts
|

Compounds Derived from Garlic as Bud Induction Agents in Organic Farming of Table Grape

Abstract: A B S T R A C TViticulture is one of the most important economic activities in the Northwest of Mexico. A major obstacle for the economic production is the insufficient period of chilling temperatures. This problem leads to poor budbreak, which in turn results in reduced yields. This problem is aggravated when plants are cultivated using the organic farming system, mostly because there are not organically approved restbreaking agents. In this work different products derived from garlic (Allium sativum L.) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…Similar satisfactory results were also obtained by using garlic-derived compounds in Perlette and Flame Seedless grapevines without exposure to chilling (Vargas et al, 2008). Both studies were done using cuttings, forced under controlled conditions.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar satisfactory results were also obtained by using garlic-derived compounds in Perlette and Flame Seedless grapevines without exposure to chilling (Vargas et al, 2008). Both studies were done using cuttings, forced under controlled conditions.…”
Section: Introductionsupporting
confidence: 65%
“…Also, Hartmann et al (2000) attributed the effect of interrupting the dormancy of different species of deciduous plants to substances with sulfur molecules. Different sulfur compounds are components of GC, which were previously reported (Vargas et al, 2008). The mechanism by which sulfur compounds can induce bud breaking continues to be unknown.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, Huang et al (2012) described DMDS as an elicitor of induced systemic resistance in N. benthamiana against Botrytis cinerea. Additionally, S-containing VOCs seem to enhance grape vine bud break (Kubota et al, 2003;Vargas-Arispuro et al, 2008). Whether DMDS mediates signaling processes involved in plant defense in N. attenuata is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The active substances from garlic responsible for breaking bud dormancy in grapevines are sulfur-containing compounds containing an allyl group (CH 2 CHCH 2 ), particularly DADS. Many researchers have demonstrated that garlic extracts or the sulfur-containing compounds of garlic can improve bud break in grapevines (Kubota et al, 2003 ; Potjanapimon et al, 2008 ; Vargas-Arispuro et al, 2008 ; Botelho et al, 2010 ). Garlic and onion extracts can hasten floral bud break and increase the bud break percentage, fruit set, the total number of fruits and the fruit yield of apple trees; onion extracts can also stimulate the accumulation of total indoles (precursors for auxin synthesis) in “Anna” apple fruits (Botelho and Muller, 2007 ; Perussi et al, 2010 ; El-Yazal and Rady, 2014 ; Rady and El-Yazal, 2014 ).…”
Section: Introductionmentioning
confidence: 99%